Analisis Lagu "Komang" Karya Raim Laode Menggunakan Pendekatan Ekspresif - Siregar, Alpian (Literasi: Jurnal Pendidikan Guru Indonesia, 2024)
This study analyzes the lyrics of the song "Komang" by Raim Laode through an expressive approach, examining how the lyrics express the emotions and meanings contained therein. The analysis focuses on the use of diction, metaphors, and images that build the atmosphere and convey the personal message of the songwriter. The results of the analysis show that "Komang" expresses deep longing, affection, and appreciation for the figure of "Komang" who is personified as something valuable and gives peace. The expressive approach allows for a deeper understanding of Raim Laode's emotions and personal experiences as expressed in the lyrics of the song, beyond mere literal interpretation. This journal also discusses the implications of the expressive approach in understanding musical works of art, especially in the context of personal and emotional song lyrics.